1997
DOI: 10.1038/ki.1997.103
|View full text |Cite
|
Sign up to set email alerts
|

Renal afferent impulses, the posterior hypothalamus, and hypertension in rats with chronic renal failure

Abstract: Hypertension in 5/6 nephrectomized (CRF) rats is partly related to increased activity of the sympathetic nervous system. We have previously shown a greater norepinephrine turnover rate in the posterior hypothalamic nuclei and locus coeruleus of CRF than control rats. Dorsal rhizotomy prevented the rise in blood pressure and the increase in NE turnover rate in the posterior hypothalamus and the locus coeruleus. The studies suggest that afferent impulses from the kidney to central integrative structures in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
123
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 22 publications
7
123
0
2
Order By: Relevance
“…The same group showed that acute renal injury by intrarenal injection of phenol caused an immediate rise in blood pressure and in norepinephrine secretion from the posterior hypothalamus that could be prevented by renal denervation. 15 Thus, afferent impulses from the diseased kidney to central integrative structures in the brain may cause increased sympathetic nerve discharge and contribute to hypertension in chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…The same group showed that acute renal injury by intrarenal injection of phenol caused an immediate rise in blood pressure and in norepinephrine secretion from the posterior hypothalamus that could be prevented by renal denervation. 15 Thus, afferent impulses from the diseased kidney to central integrative structures in the brain may cause increased sympathetic nerve discharge and contribute to hypertension in chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that sympathetic overactivity is explained by increased afferent signals emanating from the kidney (43). In models of renal failure, one finds release not only of catecholamines but also of co-transmitters (44), and both may account for accelerated progression.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…Experimental data have indicated that the presence of parenchymal injury results in neurogenic hypertension (3). Muscle sympathetic nerve activity (MSNA) is increased in both dialysis and predialysis patients, whereas bilaterally nephrectomized patients have MSNA identical to control subjects (4 -6).…”
mentioning
confidence: 99%